Telecommunication Sector and Foreign Direct Investment: An Indian Perspective - Mahajan, Dinesh (Journal of Commerce and Trade, 2014)
A paradigm shift has occurred in the telecommunication sector after 1991. After the liberlisation measures taken in 1991, this sector has brought revolution in the history of India. In this study an attempt has been made to assess the existing scenario of FDI in the telecommunication sector and to analyse the FDI inflows in this sector. The study reveals that FDI inflows have increased from Rs. 685.54 crores in 2000 to Rs. 1,770 crores in 2013. This sector is mainly dominated by Mauritius and followed by Singapore, Russia, Japan and U.S.A. The major share in FDI inflows in this sector is attracted by New Delhi region. No doubt much progress has been made in urban areas and metros in the telecommunication sector but still there exists a lot of scope for this sector in semi urban and rural areas.